Impact of Mating Methods and Semen Preservation on Reproductive and Growth Performances in Palestinian Assaf Sheep - Wael Halaweh; Samia Khnissi; Ikram Ben Souf; Muayad Salman; Naceur M’Hamdi (Biology)
As global demand for sheep products increases, improving reproductive efficiency and lamb growth performance has become a priority for sheep farmers. Artificial insemination (AI) offers several advantages over natural mating, including improved genetic selection and disease control. This study contributes to understanding the impact of different mating methods and semen preservation techniques on reproductive performance and growth traits in Palestinian Assaf sheep under local breeding conditions. The research included 123 adult Assaf ewes from two farms, which were hormonally synchronized and divided into three groups for different reproductive biotechnologies. Group 1 (G1) comprised 50 ewes inseminated with frozen semen straws, while Group 2 (G2) had 37 ewes inseminated with fresh semen from genetically superior rams. Both G1 and G2 used 0.5 mL straws containing 250 million sperm, with insemination occurring 48 h post sponge removal and eCG hormone injection. Group 3 (G3) consisted of 36 ewes that underwent natural mating at a ratio of 1 ram to 6 ewes. The study revealed that insemination methods significantly affected fertility rates (45.4, 61.1, and 71.9% for G1, G2, and G3, respectively; p < 0.05). Artificial insemination notably enhanced lamb performance indicators (p < 0.05), although it did not significantly influence prolific lambing (p > 0.05). Prolific lambing significantly impacted birth weight, weaning weight, and average daily gain at 60 days across all groups (p < 0.05), but not the average daily gain or final weight at 180 days (p > 0.05). The management system significantly affected birth and weaning weights at 60 days (p < 0.05), but not the final weight at 180 days or prolific lambing (p > 0.05). Lamb sex significantly influenced average daily gains at 60 and 180 days, as well as final weight at 180 days (p < 0.05). The findings suggest that, while artificial insemination with semen from elite rams may reduce fertility rates, it significantly improves lamb performance rates. In conclusion, our study demonstrates that, while natural mating offers higher fertility rates, AI with fresh semen can be a valuable tool for improving lamb growth performance in Palestinian Assaf sheep. These findings provide valuable insights for sheep farmers in the region to optimize reproductive strategies and enhance lamb production